Isolation and characterisation of transcripts for LEAFY, GLOBOSA and DROOPING LEAF transcription factors from normal and mantled oil palm inflorescence - Vetaryan, Sharmilah (2018)
Flowering is a crucial process in plants to ensure the continuity of species. It is a highly regulated process of which transcription factors play a major role from initiation of the reproductive development until production of fruits. In oil palm clonal planting materials, somaclonal variation in flower development was observed, notably mantling abnormality in which feminization of male flower structures occur. Consequently, production of fruit is affected and oil yield is jeopardized. The objective of this study was to investigate the possible function and also association of LEAFY(LFY), GLOBOSA (GLO) and DROOPING LEAF(DL) transcription factor genes with the mantling phenomena. Transcripts and transcript variants of these genes were isolated and their expression patterns were characterised in oil palm organs, developing female inflorescence, as well as normal and mantled inflorescence via quantitative PCR. Furthermore, selected transcripts were analysed with RNA in situ hybridisation. Two transcripts each of EgLFY, EgGLO and EgDL were isolated. Additionally, a splice variant was isolated for both EgLFY and EgGLO respectively. Both splice variants, EgLFY2v and EgGLO1v, have an intron and a premature stop codon. Tissue-specific expression analysis showed that EgLFY, EgGLO and EgDL were expressed in apical meristem tissue, whereas EgLFY and EgGLO are expressed in both male and female inflorescences at stage 2 of development. Further analysis on expression trend of transcripts at stage 1 to stage 4 of developing female inflorescence series revealed accumulation of EgLFY transcripts are at its highest at stage 1, whereas EgDL expression begins at stage 3 and increases steeply at stage 4. Meanwhile, the expression of EgGLO was constant throughout the developmental stages. Comparative expression analysis between normal and mantled inflorescence showed that EgLFY1 transcript abundance observed in mantled inflorescence was only 75% of that of in normal inflorescence at stage 1 of development whereas, the expression of EgDL1 and EgDL2 was slightly higher than 2-fold in mantled inflorescence at stage 4 of development. However only differential expression of EgLFY1 was statistically significant. Furthermore, RNA in situ hybridisation of EgDL1 revealed expression of the transcript in the ectopic supplementary carpels of mantled inflorescence. Duplication of genes might have arisen through segmental duplication which is widespread in oil palm species. Expression of EgLFY, EgGLO and EgDL transcripts in apical meristem indicates that these transcripts may play an additional role in vegetative growth in oil palm. All three TFs also play crucial role during initiation and development of oil palm inflorescence. Based on the qPCR and RNA in situ hybridisation expression results, it was postulated that EgLFY1 and EgDL1 are associated to the mantling abnormality in clonal palms. The findings enabled the identification of transcripts which has the potential to be developed as markers for mantling floral abnormality.